FDG PET/CT appearance of portal vein tumor thrombus in the gastric primitive neuroectodermal tumor: uncommon primary tumor site with rare finding. - (:unkn) unknown (My University, 2013)
Gastric primitive neuroectodermal tumor (PNET) is a very rare tumor. There are only a few case reports in the literature. Although cases with FDG uptake in the portal venous tumor thrombus (PVTT) in different primary malignancies have been evaluated before, the coexistence of PNET and PVTT has not been reported yet. Herein, we report the case of a gastric PNET with PVTT, which resolved after 3 cycles of polychemotherapy except for a residual tumor focus in the gastric corpus.